MANAJEMEN PEMUATAN KAPAL MOTOR PENYEBERANGAN PRATHITA IV DI PELABUHAN ASDP KETAPANG - Aan Rubiyanto; Eni Tri Wahyuni (LPPM STIE DHARMAPUTRA SEMARANG, 2022)
ABSTRACTThis writing aims to find out how the correct procedure is when loading according to the operating standards applied at the ASDP Ketapang harbor, as well as to find out the performance of operational officers in the field, what if deviates from the loading procedure, thus endangering safety. The data analysis used is a qualitative approach to primary data through interviews and observations and secondary data in the study of legislation and books related to this research. This observation was carried out at the ASDP Ketapang harbor. One of the ships operating at the ASDP Ketapang harbor is KMP. PRATHITA IV, which is managed by PT. ASDP “Indonesia Ferry” (Persero). Based on the research, it can be concluded about the management of motorized boat loading for the KMP crossing. Prathita IV at the ASDP Ketapang port in providing services there are still some discrepancies between procedures and reality, including the occurrence of passengers who choose to stay in their vehicles when the ship sails. In the discussion of the problem, it is explained that they must lean according to loading hours, passengers are prohibited from being in their vehicles when the ship is sailing, and additional loading and unloading time on operating ships so that the implementation of lashing and manifest recording can be carried out optimally. Keywords: Loading, Service, Safety, Standard Operating Procedure ABSTRAKPenulisan ini bertujuan untuk mengetahui bagaimana prosedur yang benar saat pemuatan menurut standar operasi yang diterapkan di Pelabuhan ASDP Ketapang, juga untuk mengetahui kinerja petugas operasional dilapangan, apa saja yang sekiranya menyimpang dari prosedur pemuatan, sehingga membahayakan keselamatan. Analisis data yang digunakan adalah pendekatan kualitatif terhadap data primer melalui wawancara dan observasi dan data sekunder dalam kajian perundang-undangan dan buku yang terkait dengan penelitian ini. Pengamatan ini dilakukan di Pelabuhan ASDP Ketapang. Salah satu kapal yang beroperasi di Pelabuhan ASDP Ketapang yaitu KMP. PRATHITA IV, yang dikelola oleh PT. ASDP “Indonesia Ferry” (Persero). Berdasarkan penelitian dapat disimpulkan mengenai manajemen pemuatan kapal motor penyeberangan KMP. Prathita IV di pelabuhan ASDP Ketapang dalam memberikan pelayanan jasa masih terdapat beberapa ketidak sesuaian antara prosedur dan kenyataan, diantaranya yaitu terjadinya penumpang yang memilih menetap di kendaraan mereka pada saat kapal berlayar. Dalam pembahasan masalah dijelaskan bahwa itu harus sandar sesuai jam muat, penumpang dilarang berada di dalam kendaraan mereka pada saat kapal berlayar, dan penambahan waktu bongkar muat pada kapal yang beroperasi agar pelaksanaan lashing dan pencatatan manifest dapat dilaksanakan secara maksimal. Kata Kunci : Pemuatan, Pelayanan, Keselamatan, Standar Operasional Prosedur